Strategi Guru Dalam Pembelajaran Menghafal Juz Amma pada Anak Usia Dini di TK Plus Hasyim Asy’ari Pikatan Blitar - Indria Neng Putri; Luk-luk Nur Mufidah (Gerasi Insan Nusantara, 2023)
This research is based on the condition of researchers in the field that there are at least some Qur'ani programs in early childhood education institutions because of the limited facilities and infrastructure that are inadequate at the institution. The research focus of this thesis is: (1) How is the teacher planning in learning to memorize juz 'amma in early childhood at TK Plus Hasyim Asy'ari Pikatan? (2) How is the implementation of the teacher in learning to memorize juz 'amma in early childhood at TK Plus Hasyim Asy'ari Pikatan? (3) How is the teacher's evaluation in learning to memorize juz 'amma in early childhood at TK Plus Hasyim Asy'ari Pikatan?. The purpose of this study is to find out the strategies used by teachers in learning to memorize juz 'amma, as well as to provide inspiration or reference for other early childhood education institutions that the limitations that exist in the institution do not make it an obstacle for educators to be able to teach the Qur'an. 'an to students well. This study uses a qualitative approach. The type of research used is field research (field research).